Pergeseran Makna Carok Bagi Masyarakat Pulau Sapudi Kabupaten Sumenep Madura 1970 – 2010 - *, Supriyadi; Ardhana, I Ketut; Ayu Rai Wahyuni, Anak Agung (Humanis, 2017)
Bas kally every culture has rules that apply. To people who embrace the culture, as well as the culture carok in Madura.this culture was originaly to have rules and methods applicabe for ad herents. For exsemple: the ritual, then only about ho nor wemen who can couse carok. But now it began to erode any of the above, it is due to cack of public know ledge Madura againt carok actual ordinanes, carok is bascally a fight thay has been overshad owed by the abuse of dignity of women and the approval of his opponeny. In contrast to carok happens now, with out the consent and with out the above back groud, so that the meaning is in the curren carok certainly been a shit very for from the actual meaning carok.
Keywords: Carok, Culture, shifting